2012
DOI: 10.1097/aog.0b013e3182475f8a
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Hypothermia During Cytoreductive Surgery for Ovarian Cancer and Perioperative Morbidity

Abstract: Surgical hypothermia is an independent predictor of early perioperative complications and overall survival after cytoreductive surgery for ovarian cancer. This is a critically important finding, because maintaining normothermia is an inexpensive modifiable factor, which could result in reduced morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Notably, 50% of cases and 54.8% of controls experienced an end-operating body temperature of ≤36°C. While this factor was not different between cases and controls, the rate of hypothermia is substantial and may be a modifiable risk factor for overall surgical complications [44]. …”
Section: Resultsmentioning
confidence: 99%
“…Notably, 50% of cases and 54.8% of controls experienced an end-operating body temperature of ≤36°C. While this factor was not different between cases and controls, the rate of hypothermia is substantial and may be a modifiable risk factor for overall surgical complications [44]. …”
Section: Resultsmentioning
confidence: 99%
“…Several meta‐analyses and RCTs have demonstrated that preventing inadvertent hypothermia during major abdominal surgery significantly reduces wound infections, cardiac complications, bleeding and transfusion requirements, and improves immune function, the duration of post‐anaesthetic recovery and overall survival . Therefore, it makes sense to prevent the loss of body heat as also recommended by the ERAS society.…”
Section: Part B Intraoperative and Postoperative Eras Elementsmentioning
confidence: 99%
“…Clinical studies in cancer patients have confirmed an association between perioperative factors such as hypothermia 37 , blood loss 38,39 , and postoperative infections 40,41 , and increased cancer recurrence and reduced cancer-specific survival following cancer surgery.…”
Section: Introductionmentioning
confidence: 97%